2023
DOI: 10.3390/jcdd10020046
|View full text |Cite
|
Sign up to set email alerts
|

Role of Echocardiography in Diabetic Cardiomyopathy: From Mechanisms to Clinical Practice

Abstract: It has been well established that diabetes mellitus (DM) is considered as a core risk factor for the development of cardiovascular diseases. However, what is less appreciated is the fact that DM may affect cardiac function irrespective of cardiac pathologies to which it contributes, such as coronary artery disease and hypertension. Although echocardiography provides accurate and reproducible diagnostic and prognostic data in patients with DM, its use in these patients is still underappreciated, resulting in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 117 publications
0
5
0
Order By: Relevance
“…This latter parameter refers to diastolic dysfunction, which is known to be associated with lipid-induced (diabetic) cardiomyopathy. 26 Importantly, KLR or NMN supplementations reversed/prevented these indicators of cardiac dysfunction (Figure 8I and 8J; Figure S18), suggesting that v-ATPase assembly strategies may be of clinical relevance. These beneficial KLR actions were lost in the presence of rapamycin or BafA (Figure 8I; Figure S18), and those of NMN were lost in V 1 G1-mHet mice but less in V 0 d2-mHom mice (Figure 8K and 8L; Figure S18).…”
Section: V-atpase Assembly Strategies Ameliorate Lipid-induced Cardia...mentioning
confidence: 95%
“…This latter parameter refers to diastolic dysfunction, which is known to be associated with lipid-induced (diabetic) cardiomyopathy. 26 Importantly, KLR or NMN supplementations reversed/prevented these indicators of cardiac dysfunction (Figure 8I and 8J; Figure S18), suggesting that v-ATPase assembly strategies may be of clinical relevance. These beneficial KLR actions were lost in the presence of rapamycin or BafA (Figure 8I; Figure S18), and those of NMN were lost in V 1 G1-mHet mice but less in V 0 d2-mHom mice (Figure 8K and 8L; Figure S18).…”
Section: V-atpase Assembly Strategies Ameliorate Lipid-induced Cardia...mentioning
confidence: 95%
“…Recent studies have shown widely usage of strain echocardiography in detecting cardiotoxicity of cancer patients [15] as well as inflammatory and infiltrative diseases like arthritis rheumatoid, Behcet's disease and amyloidosis [16][17][18]. It has been also used in diabetic patients to evaluate diabetic cardiomyopathy in some studies [19,20]. According to higher risk of cardiovascular problems in patients with DFU, early detection of cardiac dysfunction in this population was a major concern for us.…”
Section: Plos Onementioning
confidence: 99%
“…The estimated prevalence of LV hypertrophy is approximately 70% in adult patients with DM [ 27 ]. Chronic hyperglycemia, insulin resistance, hyperinsulinemia, impaired insulin metabolic signaling, increased oxidative stress, metabolic imbalance, inflammation, inadequate immune response, microvascular dysfunction, activation of renin-angiotensin-aldosterone system, and sympathetic nervous system, and accumulation of advanced glycation end-products can all adversely affect cardiac function, resulting in DiaCM [ 21 , 26 , 28 ]. Abnormal LV remodeling is associated with longstanding glycemic abnormalities, and the longer duration of abnormal glucose control, the worse the degree of LV hypertrophy and diastolic dysfunction [ 29 ].…”
Section: Cardiovascular Diseases Associated With Diabetes Mellitusmentioning
confidence: 99%